2023
DOI: 10.20944/preprints202301.0292.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Internet Gaming Disorder among Residents in Saudi Arabia: A Cross-Sectional Study

Abstract: Objective: Internet gaming disorder (IGD) is an emerging psychiatric disorder that has received attention over the past decade. Few studies have attempted to describe this disorder in the Saudi population. This study aimed to examine the prevalence of IGD and associated factors. A cross-sectional study was conducted using translated Arabic and a validated questionnaire targeting both genders in Saudi Arabia. Methodology: A cross-sectional study using a validated questionnaire (IGD-20) and targeting Arabic-spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
0
1
Order By: Relevance
“…Further, those who played for 7-19 h per week followed closely in terms of their mean IGD score, and an additional 17% of them fell in the disordered gamers' group (derived from Table 2). These findings were not surprising given that several previous studies have linked gaming duration to higher IGD severity 7,59,60 . In their meta-analysis of 155 studies on adolescents and young adults from 33 countries, Gao et al 9 also found time spent on playing as an important risk factor along with other psychosocial factors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Further, those who played for 7-19 h per week followed closely in terms of their mean IGD score, and an additional 17% of them fell in the disordered gamers' group (derived from Table 2). These findings were not surprising given that several previous studies have linked gaming duration to higher IGD severity 7,59,60 . In their meta-analysis of 155 studies on adolescents and young adults from 33 countries, Gao et al 9 also found time spent on playing as an important risk factor along with other psychosocial factors.…”
Section: Discussionsupporting
confidence: 57%
“…Together, the present findings and those of previous studies and meta-analyses suggest that we need to be mindful of the amount of time young individuals spend on gaming, as it is a strong risk factor for developing IGD. Further, while the negative effects of gaming for > 20 h a week are quite evident 7 , the present results suggest that there still may be hope for the 7-19 h group because though they may be at risk of IGD, there is still hope for timely preventive intervention for most of them.…”
Section: Discussioncontrasting
confidence: 49%